A highly asymmetric interfacial superstructure in WC: expanding the classic grain boundary segregation and new complexion theories. Issue 1 (21st August 2019) - Luo, Zhishan; Hu, Chongze; Xie, Lin; Nie, Hongbo; Xiang, Congying; Gu, Xinfu; He, Jiaqing; Zhang, Wenqing; Yu, Zhiyang; Luo, Jian
Abstract : The discovery of a grain boundary superstructure with highly asymmetric and off-the-center segregation, along with interfacial disordering and symmetry change on the opposite sides, extends our knowledge of grain boundary segregation and complexions. Abstract : Solute segregation (adsorption) at grain boundaries (GBs), which is ubiquitous in polycrystalline materials and can remarkably alter various properties, is one of the classic materials science problems. Despite decades of research, the understanding of the atomic level GB segregation structures is still limited, mostly to symmetric GBs. Here, we combine aberration-corrected electron microscopy and first-principles calculations to reveal a highly asymmetric interfacial superstructure in WC. Several striking features are observed concurrently at this GB. First, the segregations of Ti and Co are highly asymmetric. Second, the maxima of the Ti and Co adsorption profiles are both off the center in the opposite sides, separated by an intermediate W-rich atomic layer with much less adsorbates. Third, accompanying asymmetric interfacial structural transitions occur to form a cubic-TiC-like interfacial layer on the one side and a partially disordered Co-rich segregation layer on the other side. Such a highly asymmetric interfacial superstructure knowingly differs from all prior experimental observations and is beyond the predictions of any existing models. Thus, this observation extends both the classic GB segregation models and the new complexion theory. First-principles calculations further verified all observed phenomena and provided new insights based on the analysis of differential charge transfer and bond ordering. A new descriptor, sum of bond ordering, is introduced to predict the segregation trend in complicated interfacial structures.